2017
DOI: 10.3892/mmr.2017.7838
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in serum MFG-E8, TGF-β1 and correlation to the severity of atherosclerosis determined by ultrasound

Abstract: Atherosclerosis (AS) is an age‑related inflammatory disease. Globule‑epidermal growth factor‑8 (MFG‑E8) and transforming growth factor-β1 (TGF‑β1) are involved in the pathogenesis of AS. However, age‑related changes in circulating levels of MFG‑E8 and TGF‑β1, and their correlation with the severity of AS is not well‑characterized. In this study, we investigated age‑related changes in serum levels of MFG‑E8, TGF‑β1 and examined their association with the severity of AS. Sixty healthy volunteers were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In contrast, because adiponectin and leptin are adipokines closely linked to lipid metabolism, these markers had a lower correlation with glucose level [ 8 ], which is the major component of metabolic syndrome. MFG-E8 also had a significant association with pulse wave velocity in this study, which is in accordance with the results of previous studies, suggesting that MFG-E8 could be a promising diagnostic biomarker in vascular disease [ 19 - 22 ]. It is suggested that MFG-E8 cause an age-associated increase in extracellular matrix adhesion molecules.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, because adiponectin and leptin are adipokines closely linked to lipid metabolism, these markers had a lower correlation with glucose level [ 8 ], which is the major component of metabolic syndrome. MFG-E8 also had a significant association with pulse wave velocity in this study, which is in accordance with the results of previous studies, suggesting that MFG-E8 could be a promising diagnostic biomarker in vascular disease [ 19 - 22 ]. It is suggested that MFG-E8 cause an age-associated increase in extracellular matrix adhesion molecules.…”
Section: Discussionsupporting
confidence: 93%
“…When WT mice were infused with Ang II, NF-кB was 32 markedly increased in WT but not in KO, suggesting that MFG-E8 is an important intermediary of NF-кB signaling. Several studies indicate that NF-кB activation facilitates the production of MCP1, TNF-α, ICAM1, and VCAM1 during the processes of arterial inflammation and remodeling 14,23-25,33-37 . The upregulation of MCP1 and TNF-α is higher in WT mice than in KO suggesting MFG-E8 involvement.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known to be involved in inflammatory vascular conditions 7-13 . Prior in vivo studies have demonstrated that the MFG-E8 protein increases during arterial aging and arterial injury, and in hypertensive, diabetic, and atherosclerotic arterial walls 7-12,14 . Additionally, MFG-E8 is a pivotal relay element within the Ang II/monocyte chemoattractant protein-1 (MCP1) signaling cascade that mediates VSMC proinflammation, invasion and proliferation 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…MFGE8, a secreted glycoprotein, is associated with a variety of pathophysiological processes, including anti-inflammatory [11], antifibrosis [12], antiatherosclerosis [13], and inhibition of cardiac hypertrophy [14]. Recent studies have shown that MFGE8 is a part of the arterial inflammatory signaling network that promotes endothelial cell apoptosis [15].…”
Section: Discussionmentioning
confidence: 99%